Flow-Induced Transcriptomic Remodeling of Endothelial Cells Derived From Human Induced Pluripotent Stem Cells - Helle, Emmi; Ampuja, Minna; Antola, Laura; Kivelä, Riikka (Frontiers in Physiology, 2020)
The vascular system is essential for the development and function of all organs and tissues in our body. The molecular signature and phenotype of endothelial cells (EC) are greatly affected by blood flow-induced shear stress, which is a vital component of vascular development and homeostasis. Recent advances in differentiation of ECs from human induced pluripotent stem cells (hiPSC) have enabled development of in vitro experimental models of the vasculature containing cells from healthy individuals or from patients harbouring genetic variants or diseases of interest. Here we have used hiPS-derived ECs and bulk- and single-cell RNA sequencing to study the effect of flow on the transcriptomic landscape of hiPSC-ECs and their heterogeneity. We demonstrate that hiPS-ECs are plastic and they adapt to flow by expressing known flow-induced genes. Single-cell RNA sequencing showed that flow induced a more homogenous and homeostatically more stable EC population compared to static cultures, as genes related to cell polarization, barrier formation and glucose and fatty acid transport were induced. The hiPS-ECs increased both arterial and venous markers when exposed to flow. Interestingly, while in general there was a greater increase in the venous markers, one cluster with more arterial-like hiPS-ECs was detected. Single-cell RNA sequencing revealed that not all hiPS-ECs are similar even after sorting, but exposing them to flow increases their homogeneity. Since hiPS-ECs resemble immature ECs, they provide an excellent model to study vascular development and maturation, which, as we demonstrate here, can be induced by exposing them to flow.